Characterization of distinctiveness in existing genetic resources of long melon (Cucumis melo var. utilissimus L.) by using morphological markers - Suman Poonia; Aastik Jha; C. N. Ram; Virendra Kumar; Shyam Praksah; khil Kumar Chaudhary (The Bioscan, 2025)
The present investigation was carried out for successive two years during summer season of 2023 to 2025 to carry out characterization of 39 genotypes (27 F1 + 12 parents) including 1 check of long melon (Cucumis melo var. utilissimus L.) at Main Experimental Research Station, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya, Uttar Pradesh India. The seed materials for the present investigation comprised nine lines (NDLM-23-1, NDLM-23-2, NDLM-23-3, NDLM-23-4, NDLM-23-5, NDLM-23-6, NDLM-23-7, NDLM-23-8, NDLM-23-9), three tester (Kashi Santusthi, Punjab Long Melon, Kashi Vidhi) and 27 hybrids. The field experiment was laid out in a randomized block design with three replications and 16 morphological characters studied. The study highlights significant genetic diversity among long melon genotypes, which is crucial for breeding programs aimed at improving yield, quality, and resilience to various stresses. These findings demonstrate the potential for developing superior long melon varieties through targeted breeding strategies aligned with specific cultivation methods and market demands. Future investigations should prioritize testing these genotypes across a range of environmental conditions to ensure consistent performance. Additionally, the morphological traits of existing varieties were thoroughly characterized to confirm the uniqueness of the candidate variety, enabling their use as reference material for variety protection under the PPV&FR Act.